2015
DOI: 10.3184/174751915x14446446579178
|View full text |Cite
|
Sign up to set email alerts
|

Stability of Tungsten Oxide Nanoparticles in Different Media

Abstract: Tungsten oxide (WO3) nanoparticles were synthesised by a simple chemical precipitation method in various media, such as acidic, basic and neutral. Hydrochloric acid and sodium hydroxide were used to maintain the different pH levels and tungstic acid was used as the precursor for the synthesis of tungsten oxide. The resultant nanoparticles were studied by different characterisation techniques. Powder X-ray diffraction shows that the average crystallite size of the WO3 is about 13 nm and exhibits stable orthorho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“… 27 A midrange band at 1639.39 cm −1 was noted, possibly originating from the bending of H–O–H coordinated H 2 O molecule. 28 Peak at 1379.79 cm −1 was ascribed to the presence of surface –OH groups in M–OH (either Fe(OH) 2 or Zr(OH) 4 ). 26 An additional peak emerged at 1219.15 cm −1 , which may also be attributed to the vibrations of M–OH (either Fe(OH) 2 or Zr(OH) 4 ).…”
Section: Resultsmentioning
confidence: 99%
“… 27 A midrange band at 1639.39 cm −1 was noted, possibly originating from the bending of H–O–H coordinated H 2 O molecule. 28 Peak at 1379.79 cm −1 was ascribed to the presence of surface –OH groups in M–OH (either Fe(OH) 2 or Zr(OH) 4 ). 26 An additional peak emerged at 1219.15 cm −1 , which may also be attributed to the vibrations of M–OH (either Fe(OH) 2 or Zr(OH) 4 ).…”
Section: Resultsmentioning
confidence: 99%
“…Others showed that WO 3 nanoparticles indicated the presence of absorption peaks at 320 nm (2.7-2.9 eV) (Shukla et al 2016). By comparing the results from Ragunathan et al (2015), the absorption peaks was depicted a characteristic absorption peak at 285 nm. The results supported the level of absorption of light of both photocatalysts, which have been strongly modi ed by the calcination temperature that may have been caused by the growth of crystal structure onto its surface; this then aids their incident light irradiation.…”
Section: Optical Propertiesmentioning
confidence: 94%
“…the bending of H-O-H coordinated water molecule[23]. The presence of surface -OH groups in M-OH (either Cu(OH) 2 or Zr(OH) 4 ) was revealed by the absorption peak at the wavelength 1395.63 cm −1[22].…”
mentioning
confidence: 99%